Ein Bürger unter Bauern? Michael Pfurtscheller und das Stubaital 1750-1850 - Span, Michael (2017)
The hundred years from 1750 to 1850 were characterised by great changes, often associated with even greater catchphrases. In this study, these profound and radical changes are being looked at from a special point of view, from the perspective of a periphery that is usually not considered to be typical of the transformation processes of the so called saddle period. Multiple sources make it obvious that, on the one hand, the lived in worlds of the inhabitants of the Tyrolean Stubaital were widely and inevitably affected by "big history" (ranging from reforms of the educational system to the Napoleonic Wars and the beginning industrialisation); but that they still were, on the other hand, presented with scopes of action which they dealt with in different ways.